2021
DOI: 10.1002/jcla.23745
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a lateral flow assay for nasopharyngeal antigen detection for SARS‐CoV‐2 diagnosis

Abstract: Background SARS‐CoV‐2 has become a global pandemic due to its capacity for rapid transmission. In this context, an early and rapid diagnosis of infected patients that do not require expensive equipment or highly trained personnel is crucial in order to reduce the contagious rate. The aim of this study was to evaluate a chromatographic immunoassay's performance for the rapid diagnosis of SARS‐CoV‐antigen. Methods A cross‐sectional study included 369 adults from Western México with diagnosis or suspicion of SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
(16 reference statements)
0
17
1
Order By: Relevance
“…As a consequence, we were able to conduct 2,028 paired RT-qPCR and RADT tests directly on site and cultivate virus on the same day without prior sample freezing. While the sensitivities of other RADT vary between 24 and 93% in different studies ( 33 35 ), the reported Standard Q RADT sensitivities are mostly in the range from 68 to 90% ( 14 24 ). The overall diagnostic sensitivity observed in our study was 42.86%.…”
Section: Discussionmentioning
confidence: 98%
“…As a consequence, we were able to conduct 2,028 paired RT-qPCR and RADT tests directly on site and cultivate virus on the same day without prior sample freezing. While the sensitivities of other RADT vary between 24 and 93% in different studies ( 33 35 ), the reported Standard Q RADT sensitivities are mostly in the range from 68 to 90% ( 14 24 ). The overall diagnostic sensitivity observed in our study was 42.86%.…”
Section: Discussionmentioning
confidence: 98%
“…The specificity and sensitivity of antigen detection have been demonstrated to be highly dependent on Ct values and decreases when viral load is low. 25 , 26 Indeed, the proposed LFA was further divided according to Ct values into high, intermediate, and low subgroups. Here, the high viral load group showed a 94% sensitivity and this sensitivity decreases with low Ct values ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…A diverse range of rapid point‐of‐care antigen tests for the detection of SARS‐CoV‐2 from nasopharyngeal swabs and oropharyngeal swabs are currently available in the market. Some excellent publications have described the evaluation results for these rapid point‐of‐care assays, 17 , 18 , 19 , 20 , 21 , 22 , 23 and meta‐analyses on this topic have also been published. 15 , 16 A summary of the published data suggests that the sensitivity of these rapid point‐of‐care antigen assays is generally low, ranging from 20% to 95% depending on the assay and the virus load.…”
Section: Discussionmentioning
confidence: 99%